New Concept of Ignorance: An Islamic Epistemological Approach to The Story of Moses as Relevant Reference for Contemporary Ulama - D.I. Ansusa Putra (Islam Realitas: Journal of Islamic and Social Studies, 2019)
The understanding of knowledge in the Islamic literature is more focus on the conception of knowledge itself, such as the epistemology of ma'rifah al-Ghazali, the epistemology of Islamic science Syed Nuqaib al-Attas, and the epistemology of the Qur’an Fazlur Rahman. This article is different from the previous concept that looks at knowledge from its antonym, Ignorance (Jahiliyyah). Ignorance is the important topic of socio-religious in the Qur’an which creates new understanding in Islamic epistemological construction. This article argues that in the Qur’an antonimical perspective, Ignorance is the antonym of the word "Islam". Here, Islam has not only seen as a religious institution. Islam is the knowledge itself which full of goodness and good perspective. While Ignorance is the absence of knowledge which at the same time as a source of everything contrary to Islam as knowledge. This statement would affect the epistemological construction of science as a whole and creates a new concept in seeing Islam and everything related to it. This article analyzes the verses of the Moses story in the Qur’an through what author call the antonymy interpretation method. It mean, interpreting the Qur’an about the knowledge through the antonym of the knowledge itself, that is nescience, ignorance and idiocy. The results of this study do not emplace the ulama as guardians of religious authority as understood today, but the ulama are groups of people who have capabilities in the structuring of Islam as knowledge.Pemahaman pengetahuan dalam khazanah Islam lebih menitikberatkan pada konsepsi pengetahuan itu sendiri, seperti epistemologi ma’rifah al-Ghazali, epistemologi keilmuan Islam Syed Nuqaib al-Attas, dan epistemologi al-Qur’an Fazlur Rahman. Berbeda dari sebelumnya, artikel ini melihat pengetahuan dari antonimnya yaitu Ignorance (Jahiliyyah). Ignorance merupakan topic sosio-religi penting dalam the al-Qur’an yang melahirkan pemahaman baru dalam bangunan epistemologi Islam. Artikel ini berargumen bahwa dalam perspektif antonimimitas al-Qur’an, Ignorance adalah antonym dari kata Islam. Di sini, Islam tidak hanya dipandang sebagai institusi agama. Islam adalah pengetahuan itu sendiri yang penuh kebaikan dan cara pandang yang baik. Sebaliknya, Ignorance merupakan ketiadaan pengetahuan yang di saat yang sama merupakan sumber dari segala perilaku yang bertentangan dengan Islam pengetahuan. Pernyataan ini akan mempengaruhi bangunan epistemologi ilmu secara keseluruhan dan melahirkan konsep baru dalam melihat Islam dan segala yang berhubungan dengannya. Artikel ini menganalisis ayat-ayat kisah Musa melalui sebuah metode penafsiran lawan kata atau yang penulis sebut sebagai metode penafsiran antonimi. Artinya, menafsirkan al-Qur’an mengenai pengetahuan melalui lawan kata dari pengetahuan itu, yaitu ketidaktahuan, ignoran dan kebodohan. Hasil penelitian ini tidak menempatkan ulama sebagai penjaga otoritas agama sebagaimana yang dipahami saat ini, tetapi ulama adalah kelompok masyarakat yang punya kapabilitas dalam strukturalisasi Islam sebagai pengetahuan.